Achieving a high throughput and a low latency through a modular packet scheduler. (2018) - Casoni, Maurizio; Grazia, Carlo Augusto; Valente, Paolo
Providing QoS guarantees in a wireless environment is a challenging task because of the idiosyncrasies of the wireless media. State-of-the-art solutions for QoS provisioning over wireless links are based on cross-layering packet schedulers that deal both with the QoS guarantees and the wireless link issues. Unfortunately, such an approach is not flexible and requires technology-dependent solutions. To address these issues, we present a modular architecture which permits the use of existing high-performance packet schedulers for wired links over generic wireless technologies, as they are, and at the same time allows the flexibility to adapt to different channel conditions. We validate the effectiveness of our modular solution through a formal analysis. We also present high-throughput twin fair scheduler (HFS), a novel packet scheduler based on the modular architecture. HFS has constant execution time, accurate fairness, and low latency.